The The Whole Brain Teaching Model: How Does This Model Contribute to Social Skills in Early Childhood? - Choirun Nisak Aulina; Siti Masitoh; Fajar Arianto (IJORER : International Journal of Recent Educational Research, 2024)
Objective: This study aims to evaluate the impact of the Whole Brain Teaching Model on enhancing students' social skills. Method: A quantitative approach with experimental research methods was used, employing a one-group pretest-posttest design. The study population consisted of students from Darussalam Candi Kindergarten, Thoriqussalam Kindergarten, and Masyitoh Kindergarten in Sidoarjo Regency. Data analysis was conducted using a paired sample t-test. Result: The findings indicate significant improvements in the average pre-test and post-test scores across various dimensions: peer relationship skills increased by 1.62, self-control (self-management skills) by 1.52, academic skills by 1.58, compliance skills by 1.82, and assertion skills by 1.53. Consequently, the null hypothesis (Ho) is rejected, and the alternative hypothesis (Ha) is accepted. Therefore, the Whole Brain Teaching model positively and comprehensively enhances various aspects of social skills in early childhood. Novelty: This study showcases a unique application of the Whole Brain Teaching (WBT) Model to enhance social skills in early childhood. By adopting a holistic approach that engages both the left and right brain, the study fosters cooperation, empathy, and communication, thereby offering a fresh perspective on early childhood education.